2010
DOI: 10.1002/jat.1564
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects induced by unmodified and organically modified nanoclays in the human hepatic HepG2 cell line

Abstract: The term 'nanoclay' generically refers to the natural clay mineral, montmorillonite, with silica and alumina as the dominant constituents. The incorporation of nanoclays into polymeric systems dramatically enhances their barrier properties as well as their thermal and mechanical resistance. Consequently, nanoclays are employed in a wide range of industrial applications with recent studies reporting potential use in the modulation of drug release. With the increase in manufacturing of nanoclay-containing produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 51 publications
6
93
1
1
Order By: Relevance
“…In this sense, Cloisite s Na þ (CNa þ ) did not show signs of cytotoxicity in Caco-2 cells, although Cloisite s 30B (C30B) induced approximately 40% cytotoxicity at the highest concentration tested (226 mg/mL) after 24 h of exposure (Sharma et al, 2010). In addition, the cytotoxicity induced by CNa þ on HepG2 cells was lower than that obtained after exposure to Cloisite s 93A (C93A) for 24 h (Lordan et al, 2011). In addition, active bentonite, which is bentonite that is industrially treated with H 2 SO 4 , produced greater damage in human B lymphoblast cells than the native bentonite (Meibian et al, 2010).…”
Section: Basal Cytotoxicity Assays and Morphological Studiesmentioning
confidence: 54%
“…In this sense, Cloisite s Na þ (CNa þ ) did not show signs of cytotoxicity in Caco-2 cells, although Cloisite s 30B (C30B) induced approximately 40% cytotoxicity at the highest concentration tested (226 mg/mL) after 24 h of exposure (Sharma et al, 2010). In addition, the cytotoxicity induced by CNa þ on HepG2 cells was lower than that obtained after exposure to Cloisite s 93A (C93A) for 24 h (Lordan et al, 2011). In addition, active bentonite, which is bentonite that is industrially treated with H 2 SO 4 , produced greater damage in human B lymphoblast cells than the native bentonite (Meibian et al, 2010).…”
Section: Basal Cytotoxicity Assays and Morphological Studiesmentioning
confidence: 54%
“…Therefore, considering also environmental problems, the interest in bio-39 based materials, such as poly lactic acid (PLA) (Vert et inevitable disadvantages that include a tendency to crack (Priolo et al, 2010) and 55 potential health risks (Lordan et al, 2011). Therefore, a sound strategy consists in 56 partially replacing conventional petrol-based plastics with bio-based materials, for 57 instance, utilizing bio-coatings with the two-fold aim of improving the original 58 plastic properties and reducing the plastic use.…”
mentioning
confidence: 99%
“…Han et al, [21] working on cells from different organs concluded that the toxicity of two organoclays on the viability and membrane damage was not severe. Contrasting results were obtained by Lordan et al [22] in experiments aimed to assess the cytotoxicity of a montmorillonite and an organically modified clay by measuring liver cells function and membrane integrity. Both materials were cytotoxic but the montmorillonite gave a worse performance than the modified clay in two of the three parameters attesting the cytotoxicity.…”
Section: Introductionmentioning
confidence: 67%